Mast Cell Modulation of B Cell Responses: An Under-Appreciated Partnership in Host Defence - Palma, Alejandro M.; Hanes, Mark R.; Marshall, Jean S. (Frontiers in Immunology, 2021)
Mast cells are well known to be activated via cross-linking of immunoglobulins bound to surface receptors. They are also recognized as key initiators and regulators of both innate and adaptive immune responses against pathogens, especially in the skin and mucosal surfaces. Substantial attention has been given to the role of mast cells in regulating T cell function either directly or indirectly, through actions on dendritic. In contrast, the ability of mast cells to modify B cell responses has been much less well examined. Several lines of evidence suggest that mast cells can modify B cell development and activities substantially. Mast cells co-localize with B cells in many tissue settings and produce substantial amounts of cytokines, such as IL-6, with profound impacts on B cell development, class-switch recombination events and subsequent antibody production. Mast cells have also been suggested to modify the development and function of regulatory B cells. In this review, we bring together the critical current, clinical and laboratory information on the impact of mast cells and their mediators on B cell development and function and consider the implications of these findings on the host response to infection.